Investigating the Compatibility, Challenges and Prospects of Legal Education in ODL Institutions: The Nigerian Perspective - Agama, Ferdinand O. (West African Journal of Open and Flexible Learning, 2022)
Open and Distance Learning (ODL) provides present-day society with new means of imparting knowledge to learners. Due to its flexibility and potential cost savings, ODL delivery facilitates access to education for those whose financial and time resources inhibit their ability to pursue education through traditional modes. Presently, ODL is not yet one of the standard forms of instruction for legal education in Nigerian institutions. However, the idea of incorporating legal education in the ODL mode of teaching is becoming clearer by the day as influenced by technological and other forces. Legal education has been slow in adopting distance learning in Nigeria due, mainly, to the restrictive rules on it by the regulatory bodies. The paper investigated the compatibility of legal education in the ODL approach in the 21st Century. In a survey of a population of 97 year500 level Law students of the National Open University of Nigeria (NOUN), conducted, the majority of the interviewees believe that legal education is compatible with ODL institutions and that graduates from such institutions are not after all, less in terms of competence, character and integrity. The paper concludes that, with advancements in technology, instruction in ODL has gone beyond just talking heads on the TV screen. It argues further that ODL when carefully designed and delivered, creates a high-quality academic experience and produces learner outcomes on par, if not superior to those of conventional in-class learning. The study recommends the reconsideration of the restrictive rules on the delivery of legal education through ODL, to optimise the opportunity it offers in a technology-driven world.Résumé : La formation ouverte et à distance (FOAD) offre à la société actuelle de nouveaux moyens de transmettre des connaissances aux apprenants. Grâce à sa flexibilité et aux économies potentielles qu'elle permet de réaliser, la FOAD facilite l’accès aux nouvelles voies d'éducation à ceux dont les ressources financières et temporelles les empêchent de suivre des styles d'éducation traditionnels. Actuellement, la FOAD n'est pas encore l'une des formes d'enseignement standard pour la formation juridique dans les institutions nigérianes. Bien que ses promesses et ses perspectives de transmission du savoir soient en fait multiples, la FOAD n'a pas encore été largement adoptée au Nigeria. Cependant, l'idée d'incorporer l'enseignement juridique dans le mode d'enseignement de la FOAD devient plus claire et plus forte de jour en jour, sous l'influence de forces technologiques et autres. L'enseignement juridique a été lent à adopter l'apprentissage à distance au Nigeria, en partie à cause des règles restrictives imposées par les organismes de réglementation. Cet article constate que le souci de la qualité des résultats est au cœur de ces règles restrictives sur la FOAD dans l'enseignement juridique. L'article étudie donc la compatibilité, les défis et les perspectives de l'enseignement juridique dans l'approche de la FOAD au 21ème siècle. Il conclut qu'avec les progrès technologiques, l'enseignement et la formation en FOAD sont allés bien au-delà des simples têtes parlantes sur l'écran de télévision. Il affirme en outre que la FOAD, lorsqu'elle est conçue et dispensée avec soin, crée une expérience universitaire de haute qualité et produit des résultats pour l'apprenant équivalents, voire supérieurs, à ceux de l'apprentissage conventionnel en classe. Cette étude recommande de reconsidérer les règles restrictives de la FOAD afin d'optimiser les opportunités qu'elle offre dans un monde dominé par la technologie.Mots-clés : Apprentissage ouvert et à distance, formation juridique, compatibilité, règles restrictives, technologie
Keywords: Open and Distance Learning; Legal Education; Compatibility; Restrictive Rules; Technology